Impact of Textile Effluents on Fresh Water Fish Mastacembelus Armatus (Cuv. & Val) - S. Karthikeyan; M. Jambulingam; P. Sivakumar; A. P. Shekhar; J. Krithika (E-Journal of Chemistry)
The textile effluents has been proved to impart adverse effects on humans, animals and plantation. The present study reveals that the impact of textile effluents on a protenious edible fresh water fish Mastacembelus Armatus by examining the changes in the ionic regulations of some selected tissues like liver , kidney and muscle before and after exposure to the Acid Blue 92 (CI.No. 13390). Mastacembelus Armatus were exposed to sub lethal concentration of textile dye - Acid Blue 92 ( CI.No. 13390) for a period of 35 days. After the exposure period it was observed that a decrease in concentration of Sodium and Chloride ions and an increase in concentration of potassium, Calcium and magnesium ions. The magnesium ion concentration increased, but only slightly, when compared to the fluctuations of the other ions. The cationic concentrations of the test individuals indicate that the impact of textile effluents has an adverse effect the ionic regulations.